The impact of music preferences and engagement on emotional wellbeing among Malaysian university students - Mohamed Razali, Camellia Siti Maya; Ma’rof, Aini Azeqa (Human Resource Management Academic Research Society, 2024)
This study investigates the influence of music genre preference, frequency of music listening, active and passive music engagement, and personal connection to music on emotional wellbeing among university students in the Klang Valley, Malaysia. A quantitative approach was employed with a sample of 412 participants, utilizing Pearson correlation and multiple regression analyses to explore the relationships between these variables. The findings revealed that personal connection to music was the strongest predictor of emotional wellbeing, followed by passive music engagement, frequency of listening, active engagement, and music genre preference. These results highlight the critical role of emotional connection and both forms of music engagement in promoting emotional wellbeing among students. While music genre preference contributed to wellbeing, its influence was relatively weaker. The study suggests that educational institutions should encourage personal connection to music and create environments that facilitate both passive and active music engagement to enhance student wellbeing. Mental health practitioners and policymakers are encouraged to integrate music-based strategies as part of broader emotional wellbeing programs in university settings.